MANAJEMEN SARANA PRASARANA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD IT TIHAMAH CIREBON - syifa syahida (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
School Facilities and Infrastructure Management In terms of its function or role in the implementation of the teaching and learning process, educational facilities (material facilities) are divided into 3 types: 1). Learning tools, 2). props 3). Teaching media. . While the education sector is school buildings and school furniture in this study explains how planning, implementing and evaluating the management of facilities and infrastructure in improving the quality of education in elementary schools. 004 Bengalon East Kutai. This study uses a qualitative approach, namely a study that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of the evaluation of management of facilities and infrastructure in improving the quality of education in Elemantary school.004 Bengalon East Kutai that the process of infrastructure facilities in Elemantary School Keywords : Management of Facilities and Infrastructure, School Quality.